Relationship Between Age, Gender, Obesity, And Occupation With The Incidence Of Knee Osteoarthritis At Bhayangkara Hospital In 2023 - Indah Rusman; Andi Dhedie Prasatia Sam; Syarif Hidayatullah; Fadil Mula Putra; Erick Gamaliel Amba (Jurnal EduHealth, 2025)
Osteoarthritis (OA) is inflammation of the joints due to degenerative damage to the cartilage and surrounding tissue. The degenerative nature of osteoarthritis develop slowly, but this can cause disability and failure of joint function accompanied by pain. risk factors for OA are age, gender, genetics, obesity, ethnicity, metabolic disease, work, exercise, joint injuries, and growth disorders. Osteoarthritis can attack various joints in the body, but more often affects joints that support the body's weight, such as the knee joint and hip joint. The knee joint is a joint that is very often affected by OA. Data from the Central for Disease Control and Prevention (CDC) shows that as much as 40% of the population aged > 70 years suffer from knee OA. To determine the incidence, risk factors and relationship between risk factors for the occurrence of Knee Osteoarthritis at Bhayangkara Hospital Makassar in 2023. This Method Description research using a Cross Sectional approach. The incidence of Knee Osteoarthritis at Bhayangkara Makassar Hospital in 2023 there were 186 patients, the presentation of patient age <40 years in this study was 28.5% and >40 years is 71.5%, the gender presentation of patients in this study were male as much as 31.7% and women as much as 68.3%, the distribution of obesity in this study was 68.3% and not obese as much as 31.7%, the presentation of work patients on the incidence of osteoarthritis where in this study 33.9% worked and 66.1% did not work and there was a relationship between age, gender, obesity and work on the incidence of osteoarthritis. Based on the research results, it can be concluded that there is a relationship between age, gender, obesity and occupation with the incidence of Knee Osteoarthritis at Bhayangkara Hospital in 2023.